Electrode sheet and preparation method thereof and battery

By designing a multi-layer structure in the electrode sheet of a lithium-ion battery, including a current collector, an electrode material layer, an intermediate transition layer and a solid electrolyte layer, the safety and conductivity problems of ceramic coatings under high energy density are solved, and the high energy density and safety performance of the battery are improved.

CN119208516BActive Publication Date: 2025-03-18JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411710703.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

In the case of high energy density of existing lithium-ion batteries, the safety of the liquid electrolyte system is affected. The ceramic coating has large interface impedance and poor conductivity, which reduces the flexibility and compaction density of the electrode sheet, resulting in the inability to increase the energy density of the battery.

Method used

An electrode sheet is designed, including a current collector, an electrode material layer, an intermediate transition layer and a solid electrolyte layer. The electrode material layer and the intermediate transition layer both contain active materials and a composite solid electrolyte. The composite solid electrolyte content in the intermediate transition layer is greater than that of the electrode material layer. The solid electrolyte layer consists of an inorganic solid electrolyte and an organic solid electrolyte with lithium conduction and conductivity.

Benefits of technology

By improving the conductivity and compaction density of the electrode sheet, the migration and movement mechanical properties of lithium ions are improved, the interface impedance is reduced, and the cycle performance and safety performance of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208516B_ABST
    Figure CN119208516B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and specifically to an electrode plate, a preparation method thereof, and a battery. The electrode plate comprises: a current collector; an electrode material layer, arranged on at least one side surface of the current collector along the thickness direction; an intermediate transition layer, arranged on the surface of the electrode material layer away from the current collector, the electrode material layer and the intermediate transition layer both comprising active materials and a composite solid electrolyte; and a solid electrolyte layer, arranged on the surface of the intermediate transition layer away from the electrode material layer, the solid electrolyte layer comprising a composite solid electrolyte; the composite solid electrolyte comprises an inorganic solid electrolyte and an organic solid electrolyte having lithium and electrical conductivity; the content of the composite solid electrolyte in the intermediate transition layer is greater than the content of the composite solid electrolyte in the electrode material layer. A battery comprises the provided electrode plate. The present application can improve the migration kinetics of lithium ions, improve the conductivity and compaction density of the plate, and improve the cycle performance and safety performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an electrode plate and a preparation method thereof, and a battery. Background Art

[0002] In recent years, in order to meet the demand for battery life, the energy density of lithium-ion batteries has been significantly improved. However, this progress (that is, the progress of significantly improved energy density) has also brought some severe challenges. For example, the existing liquid electrolyte system battery, under the condition of high energy density, affects the safety of the battery. In order to alleviate this safety problem, in the related technology, ceramic is coated on the positive electrode to improve the safety performance of lithium-ion batteries, and preventing thermal runaway is the most studied method.

[0003] However, there are still some problems that need to be solved in the method of improving the safety performance of the battery by coating ceramics on the positive electrode: ① The interfacial impedance of the ceramic coating is large, which greatly reduces the migration kinetics of lithium ions; ② The conductive properties of the ceramic coating seriously affect the basic electrical properties of lithium-ion batteries, such as room temperature and high temperature cycling, rate discharge and other properties; ③ The ceramic coating reduces the flexibility of the electrode, thereby reducing the compaction density of the electrode, so that the energy density of the battery cannot be improved.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides an electrode sheet and a preparation method thereof and a battery, which are conducive to improving the conductivity and compaction density of the electrode sheet, and improving the cycle performance and safety performance of the battery.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] According to one aspect of the present application, an embodiment of the present application provides an electrode plate, wherein the electrode plate comprises:

[0008] current collector;

[0009] An electrode material layer, disposed on at least one side surface of the current collector along the thickness direction, the electrode material layer comprising an active material and a composite solid electrolyte;

[0010] An intermediate transition layer, disposed on a surface of the electrode material layer away from the current collector, the intermediate transition layer comprising an active material and a composite solid electrolyte; and

[0011] A solid electrolyte layer is arranged on a surface of the intermediate transition layer away from the electrode material layer, and the solid electrolyte layer includes a composite solid electrolyte;

[0012] Wherein, the composite solid electrolyte comprises an inorganic solid electrolyte and an organic solid electrolyte having lithium and electrical conductivity;

[0013] The content of the composite solid electrolyte in the intermediate transition layer is greater than the content of the composite solid electrolyte in the electrode material layer.

[0014] In addition, the electrode plate according to the present application may also have the following additional technical features:

[0015] In some of the embodiments, the organic solid electrolyte having lithium conductivity and electrical conductivity includes a copolymer, which is a block copolymer with an AB structure, wherein A is a conductive unit, B is a lithium conductive unit, the conductive unit includes a conductive polymer monomer, and the lithium conductive unit includes a lithium conductive polymer.

[0016] In some embodiments, the conductive polymer monomer includes at least one of pyrrole, aniline, thiophene, acetylene, p-phenylene terephthalamide, or 3,4-ethylenedioxythiophene.

[0017] In some embodiments, the lithium-conducting polymer includes at least one of polyethylene oxide, polyethylene glycol, polypropylene oxide, poly(ethylene glycol) acrylate or poly(ethylene glycol) methacrylate.

[0018] In some of the embodiments, in the electrode material layer, the mass proportion of the composite solid electrolyte is 0.1% to 5%, and the mass proportion of the active material is 95% to 99.9%.

[0019] In some of the embodiments, in the intermediate transition layer, the mass proportion of the composite solid electrolyte is 20% to 80%, and the mass proportion of the active material is 20% to 80%.

[0020] In some of the embodiments, the inorganic solid electrolyte includes an oxide solid electrolyte.

[0021] In some embodiments, the oxide solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide or lithium lanthanum titanate.

[0022] In some embodiments, the active material is a positive electrode active material or a negative electrode active material.

[0023] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium cobalt manganese oxide, lithium cobalt nickel oxide, lithium nickel manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.

[0024] In some embodiments, the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, lithium titanate or silicon-based materials.

[0025] In some of the embodiments, in the composite solid electrolyte in the electrode material layer, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is x, and x is (5-95): (95-5).

[0026] In some of the embodiments, in the composite solid electrolyte in the intermediate transition layer, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is y, and y is (5-95): (95-5).

[0027] In some embodiments, in the composite solid electrolyte in the solid electrolyte layer, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is z, and z is (5-95): (95-5);

[0028] In some of the embodiments, said x, said y and said z are the same.

[0029] In some embodiments, the electrode material layer has a thickness of 30 μm to 150 μm.

[0030] In some embodiments, the intermediate transition layer has a thickness of 0.1 μm to 5 μm.

[0031] In some embodiments, the solid electrolyte layer has a thickness of 0.5 μm to 5 μm.

[0032] According to another aspect of the present application, an embodiment of the present application provides a method for preparing an electrode sheet, the method comprising the following steps:

[0033] Providing electrode material layer slurry and solid electrolyte layer slurry respectively;

[0034] sequentially coating the electrode material layer slurry and the solid electrolyte layer slurry on the current collector to obtain an initial electrode sheet;

[0035] The initial electrode sheet is dried and hot rolled, and an electrode material layer, an intermediate transition layer and a solid electrolyte layer are sequentially formed on the current collector to obtain an electrode electrode sheet, wherein the intermediate transition layer is formed by the solid electrolyte layer slurry coated on the electrode material layer penetrating into the electrode material layer.

[0036] In some embodiments, the preparation method satisfies at least one of the following features (1) to (8): (1) the solvent in the electrode material layer slurry includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, acetone or water; (2) the solvent in the solid electrolyte layer slurry includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, ethanol or acetone; (3) the solid content of the electrode material layer slurry is 50% to 85%, and the viscosity is 1500 to 8000 mPa·s; (4) the solid content of the solid electrolyte layer slurry is 25% to 45%, and the viscosity is 100 to 2000mPa·S; (5) the drying temperature is 50℃~130℃; (6) in the initial pole piece, the thickness of the electrode material layer is 50μm~200μm; and / or, in the electrode pole piece, the thickness of the electrode material layer is 30μm~150μm; (7) in the initial pole piece, the thickness of the intermediate transition layer is 0.1μm~10μm; and / or, in the electrode pole piece, the thickness of the intermediate transition layer is 0.1μm~5μm; (8) in the initial pole piece, the thickness of the solid electrolyte layer is 1μm~10μm; and / or, in the electrode pole piece, the thickness of the solid electrolyte layer is 0.5μm~5μm.

[0037] In some embodiments, the electrode material layer slurry and the solid electrolyte layer slurry both contain an organic solid electrolyte having lithium conductivity and electrical conductivity, and the organic solid electrolyte having lithium conductivity and electrical conductivity includes a copolymer, and the preparation of the copolymer includes:

[0038] A lithium-conducting polymer, a solvent and an isocyanate monomer are first contacted to obtain a viscous solution; the viscous solution, a conductive polymer monomer, an initiator and a solvent are second contacted to generate a polymerization reaction to obtain a first material; the first material is post-processed to obtain a block copolymer having an AB structure; wherein A is a conductive unit, B is a lithium-conducting unit, the conductive unit includes a conductive polymer monomer, and the lithium-conducting unit includes a lithium-conducting polymer.

[0039] According to another aspect of the present application, an embodiment of the present application provides a battery, the battery comprising a positive electrode sheet, a negative electrode sheet and a separator;

[0040] Wherein, the positive electrode sheet and / or the negative electrode sheet comprises the aforementioned electrode sheet or the electrode sheet prepared according to the aforementioned preparation method.

[0041] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0042] In the embodiment of the present application, the provided electrode plate includes an electrode material layer, an intermediate transition layer and a solid electrolyte layer sequentially arranged on the current collector, the electrode material layer and the intermediate transition layer both include active materials and composite solid electrolytes, and the content of the composite solid electrolyte in the intermediate transition layer is greater than the content of the composite solid electrolyte in the electrode material layer, and the solid electrolyte layer includes a composite solid electrolyte, which includes an inorganic solid electrolyte and an organic solid electrolyte with lithium and electrical conductivity. Thus, by adding a composite solid electrolyte with high ionic conductivity and electronic conductivity to the electrode material layer, the lithium ion conduction and electronic conduction efficiency of the electrode plate can be improved, and the polarization phenomenon of the positive and negative electrode materials at the surface and substrate of the electrode plate during the charging and discharging process of the lithium ion solid-state battery can be reduced. By arranging an intermediate transition layer between the electrode material layer and the solid electrolyte layer, the interface compatibility between the electrode material layer and the solid electrolyte layer can be improved, the interface impedance can be reduced, and the ion conduction and electronic conduction ability of lithium ions at the positive and negative electrode interfaces can be effectively enhanced. By constructing a solid electrolyte layer containing high ionic conductivity and electronic conductivity on the surface of the electrode plate, the conductivity of the electrolyte system can be further optimized, thereby improving the rate performance and cycle performance of the battery. In addition, by mixing composite solid electrolytes into the electrode plates, the use of liquid electrolytes has been successfully reduced, thereby greatly enhancing the safety performance of the battery.

[0043] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Shown is a schematic structural diagram of an electrode plate provided in an embodiment of the present invention.

[0045] Figure 2 The figure shows a schematic structural diagram of an organic solid electrolyte having lithium and electrical conductivity provided by an embodiment of the present invention.

[0046] Description of reference numerals:

[0047] 10-current collector;

[0048] 20-electrode material layer;

[0049] 30-intermediate transition layer;

[0050] 40-Solid electrolyte layer. DETAILED DESCRIPTION

[0051] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0053] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0054] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0055] As mentioned in the background art, in order to improve the safety performance of lithium-ion batteries, batteries of related technologies such as lithium-ion batteries are coated with ceramic coatings on the positive electrode plates. However, the method of setting the ceramic coatings still has certain shortcomings, such as the interface impedance of the ceramic coatings is large, the conductivity of the ceramic coatings is poor, the ceramic coatings reduce the flexibility of the plates, and reduce the compaction density of the plates, so that the energy density of the battery cannot be effectively improved, etc. Therefore, effective means are needed to alleviate the above shortcomings.

[0056] In view of this, the inventor of the present application has improved the structure or composition of the electrode plate of the battery, and through the ingenious design of the electrode plate containing the composite solid electrolyte, a simple hybrid system electrode plate and its preparation method are provided, which not only improves the safety of the battery, but also helps to improve the energy density and conductivity of the battery, and can effectively alleviate the shortcomings of the ceramic coating in the prior art, thereby effectively improving the cycle performance and safety of the battery. The present application is described in detail below.

[0057] refer to Figure 1 As shown, in some embodiments, the present application provides an electrode plate, which includes:

[0058] Current collector 10;

[0059] The electrode material layer 20 is disposed on at least one side of the current collector 10 along the thickness direction, and the electrode material layer 20 includes an active material and a composite solid electrolyte;

[0060] An intermediate transition layer 30 is disposed on a surface of the electrode material layer 20 away from the current collector 10 , and the intermediate transition layer 30 includes an active material and a composite solid electrolyte; and

[0061] The solid electrolyte layer 40 is disposed on the surface of the intermediate transition layer 30 away from the electrode material layer 20, and the solid electrolyte layer 40 includes a composite solid electrolyte;

[0062] The composite solid electrolyte includes an inorganic solid electrolyte and an organic solid electrolyte having lithium and electrical conductivity; the content of the composite solid electrolyte in the intermediate transition layer 30 is greater than the content of the composite solid electrolyte in the electrode material layer 20 .

[0063] The provided electrode plate has a multi-layer structure, which includes a current collector 10, an electrode material layer 20, an intermediate transition layer 30 and a solid electrolyte layer 40 stacked in sequence, that is, the electrode material layer 20 is arranged on at least one side surface of the current collector 10, the intermediate transition layer 30 is arranged on the surface of the electrode material layer 20, and the solid electrolyte layer 40 is arranged on the surface of the intermediate transition layer 30.

[0064] The above-mentioned “the electrode material layer 20 is disposed on at least one side surface of the current collector 10 along the thickness direction” means that the electrode material layer 20 can be disposed on one surface of the current collector 10 along its own thickness direction, or on two surfaces of the current collector 10 along its own thickness direction. The “surface” here can be the entire area of ​​the current collector 10, or a partial area of ​​the current collector 10. For example, in this embodiment, the surface can be a partial area of ​​the current collector 10, and the remaining area of ​​the current collector 10 can be used to connect the pole ear. This application has no special restrictions on this, as long as the purpose of this application can be achieved.

[0065] As an example, the current collector 10 has two surfaces opposite to each other in its own thickness direction, and the electrode material layer 20 is disposed on the two opposite surfaces of the current collector 10. Further, an intermediate transition layer 30 is formed on the surface of the electrode material layer 20 on both sides, and a solid electrolyte layer 40 is formed on the surface of the intermediate transition layer 30. It can be understood that in other embodiments, the electrode material layer 20 can also be stacked on any one of the two surfaces of the current collector 10.

[0066] In the present application, the electrode material layer 20, the intermediate transition layer 30 and the solid electrolyte layer 40 all contain a composite solid electrolyte, which is mainly composed of an inorganic solid electrolyte and an organic solid electrolyte, and the organic solid electrolyte adopts an organic solid electrolyte with lithium conductivity and electrical conductivity. Among them, the inorganic solid electrolyte has the characteristics of high stability, low cost, high strength, etc., and the inorganic solid electrolyte itself has a certain ion conductivity, which is beneficial to improve the ion conduction effect (conductivity) and mechanical strength of the pole piece. The organic solid electrolyte with lithium conductivity and electrical conductivity can simultaneously have excellent lithium conductivity and electrical conductivity, provide an effective path for the transmission of lithium ions, and is beneficial to reduce the interface transmission resistance of ions. It can reduce the interface resistance of the pole piece while improving the transmission of lithium ions in the pole piece and improving the battery rate performance. Therefore, the provided composite solid electrolyte composed of an inorganic solid electrolyte and an organic solid electrolyte with lithium conductivity and electrical conductivity has the characteristics of high ionic conductivity and electronic conductivity. When added to the electrode plate, it is beneficial to improve the lithium conductivity and electrical conductivity of the electrode plate without affecting the electrochemical performance, that is, to improve the lithium ion conduction rate and conductivity, which is beneficial to reduce the interface transmission resistance of ions, and can also improve the thermal stability and mechanical strength of the plate, thereby helping to improve the rate performance, cycle performance and safety performance of the battery.

[0067] In the present application, the electrode material layer 20 of the electrode plate contains the above-mentioned composite solid electrolyte and also contains active materials. By adding a small amount of composite solid electrolyte to the electrode material layer 20, the lithium ion conduction and electron conduction efficiency of the electrode plate can be significantly improved, and the polarization phenomenon of the positive and negative electrode materials at the surface and substrate of the plate during the charging and discharging process of the lithium-ion solid-state battery can be reduced.

[0068] In the present application, the intermediate transition layer 30 of the electrode plate is located between the electrode material layer 20 and the solid electrolyte layer 40, and the content of the active material and the composite solid electrolyte in the intermediate transition layer 30 is different from that in the electrode material layer 20. For example, the types of active materials and composite solid electrolytes in the intermediate transition layer 30 and the electrode material layer 20 can be the same, and the difference between the intermediate transition layer 30 and the electrode material layer 20 is only the difference in the content of each component in the two. In comparison, the content of the composite solid electrolyte contained in the intermediate transition layer 30 is higher, while the content of the composite solid electrolyte contained in the electrode material layer 20 is lower. Similarly, the content of the active material contained in the intermediate transition layer 30 is lower, while the content of the active material contained in the electrode material layer 20 is higher. Therefore, by introducing the intermediate transition layer 30 between the electrode material layer 20 and the solid electrolyte layer 40, the interface compatibility between the electrode material layer 20 and the solid electrolyte layer 40 can be improved, the interface impedance can be reduced, and the ion conduction and electron conduction capabilities of lithium ions at the positive and negative electrode interfaces can be effectively enhanced.

[0069] In the present application, a composite solid electrolyte layer 40 with high ionic conductivity and electronic conductivity is constructed on the surface of the electrode plate, thereby further optimizing the conductivity of the electrolyte system, thereby improving the rate performance of the battery, and by mixing the composite solid electrolyte into the electrode plate, the use of liquid electrolyte is successfully reduced, thereby greatly enhancing the safety performance of the battery. The above optimization design simultaneously improves the cycle performance and safety of lithium-ion solid-state batteries.

[0070] Therefore, based on the above, the provided electrode plate can effectively improve the migration kinetics of lithium ions, improve the conductivity of the electrode plate, and improve the compaction density of the electrode plate, thereby improving the cycle performance and battery energy density of the battery using the electrode plate as well as the safety performance of the battery.

[0071] In some embodiments, the organic solid electrolyte having lithium conductivity and electrical conductivity comprises a copolymer, which is a block copolymer having an AB structure, wherein A is a conductive unit, B is a lithium conductive unit, the conductive unit comprises a conductive polymer monomer, and the lithium conductive unit comprises a lithium conductive polymer.

[0072] In the present application, the organic solid electrolyte with lithium conductivity and electrical conductivity can adopt block copolymers, such as block copolymers with AB structure, in which A is a conductive unit and B is a lithium conductive unit. Specifically, A is a monomer of a conductive polymer and B is a lithium conductive polymer. By reacting the monomer of a conductive polymer and a lithium conductive polymer, a block copolymer with lithium conductivity and electrical conductivity properties can be generated.

[0073] In some embodiments, the conductive polymer monomer includes, but is not limited to, any one or a combination of at least two of pyrrole (Py), aniline (ANI), thiophene (TH), acetylene, p-phenylene terephthalamide (PTA), or 3,4-ethylenedioxythiophene (EDOT).

[0074] Preferably, the conductive polymer monomer is selected from one or both of aniline (ANI) and p-phenylene terephthalamide (PTA).

[0075] By selecting the above-mentioned conductive polymer monomers with good electron conductivity, the block copolymers generated after reacting with the lithium-conducting polymer can simultaneously have excellent lithium-conducting and electron-conducting abilities, and are widely available, with good application effects, and are easy to control the operating conditions of the reaction with the lithium-conducting polymer to obtain an organic solid electrolyte with excellent performance.

[0076] In some embodiments, the lithium-conducting polymer includes, but is not limited to, any one or a combination of at least two of polyethylene oxide (PEO), polyethylene glycol (PEG), polypropylene oxide (PPO), poly(ethylene glycol) acrylate (also known as poly(ethylene glycol) acrylate, PEGA), or poly(ethylene glycol) methacrylate (also known as poly(ethylene glycol) methacrylate, PEGMA).

[0077] Preferably, the lithium-conducting polymer is selected from one or more of polyethylene oxide (PEO), polyethylene glycol (PEG), and polypropylene oxide (PPO).

[0078] By selecting the above-mentioned lithium-conductive polymers with good lithium conductivity, the block copolymers generated after reacting with the conductive polymer monomers can simultaneously have excellent lithium-conducting and electron-conducting capabilities, which can improve the lithium-ion transportability in the electrode and optimize the electrochemical performance of the electrode.

[0079] For example, Figure 2 As shown, when the conductive polymer monomer is selected from ANI and the lithium conductive polymer is selected from PEG, the molecular structure diagram of the formed block copolymer (PEG-PANI) is as shown Figure 2 It should be understood that when other conductive polymer monomers and lithium conductive polymers are selected, similar structural schematic diagrams can be formed.

[0080] In some embodiments, the inorganic solid electrolyte includes an oxide solid electrolyte.

[0081] Preferably, the oxide solid electrolyte includes, but is not limited to, any one or a combination of at least two of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO) or lithium lanthanum titanate (LLTO).

[0082] The above-mentioned inorganic oxide solid electrolytes have the characteristics of high stability, low cost, high strength, etc., and the inorganic solid electrolyte itself has a certain ion conductivity, which is conducive to improving the ion conduction effect (conductivity) and mechanical strength of the electrode. In addition, compared with other inorganic solid electrolytes, the current industrialization and performance of oxide solid electrolytes fully meet the use requirements, and oxide solid electrolytes basically do not react with electrolytes and positive electrode active materials, etc., and are safe and reliable.

[0083] In the present application, the content ratio of the inorganic solid electrolyte and the organic solid electrolyte having lithium conductivity and electrical conductivity in the composite solid electrolyte can be kept consistent in each layer.

[0084] Specifically, in the composite solid electrolyte in the electrode material layer 20, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is x, where x is (5-95): (95-5); in the composite solid electrolyte in the intermediate transition layer 30, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is y, where y is (5-95): (95-5); in the composite solid electrolyte in the solid electrolyte layer 40, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is z, where z is (5-95): (95-5); preferably, x, y and z are the same.

[0085] Thus, in the composite solid electrolyte in the electrode material layer 20, the intermediate transition layer 30 and the solid electrolyte layer 40, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is (5-95): (95-5), for example, 5:95, 10:90, 15:85, 20:80, 30:70, 40:60, 50:50, 80:20, 90:10, etc. And the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte in each layer remains the same.

[0086] That is, in the composite solid electrolyte, the mass proportion of the inorganic solid electrolyte can be 5% to 95%, and the remaining proportion is the proportion of the organic solid electrolyte with lithium conductivity and electrical conductivity, and the mass proportion of the inorganic solid electrolyte and the organic solid electrolyte in the electrode material layer 20, the intermediate transition layer 30 and the solid electrolyte layer 40 is consistent. Thus, by keeping the mass proportion of the inorganic solid electrolyte and the organic solid electrolyte in each layer consistent, the constructed conductive and lithium conductive network can be kept consistent, which can improve the interface compatibility and reduce the interface impedance. On the other hand, if the ratio of the inorganic solid electrolyte to the organic solid electrolyte with lithium conductivity and electrical conductivity in the electrode material layer 20 and the solid electrolyte layer 40 is inconsistent, the ratio of the inorganic solid electrolyte to the organic solid electrolyte with lithium conductivity and electrical conductivity in the intermediate transition layer 30 cannot be determined, so it is necessary to keep the ratio of the two solid electrolytes in each layer consistent.

[0087] In the present application, the electrode plate can be a positive electrode plate or a negative electrode plate. That is, the polarity of the electrode plate can be positive or negative.

[0088] Thus, in some embodiments, when the electrode plate is a positive electrode plate, the active material is a positive electrode active material; or in other embodiments, when the electrode plate is a negative electrode plate, the active material is a negative electrode active material.

[0089] The positive electrode active material and the negative electrode active material in the present invention can be conventional materials in the art, and can be homemade or commercially available, and the present invention does not impose any particular limitation on this.

[0090] Illustratively, in some embodiments, the positive electrode active material includes, but is not limited to, any one of lithium cobaltate, lithium manganate, lithium nickelate, lithium cobalt manganate, lithium cobalt nickelate, lithium nickel manganate, lithium nickel cobalt manganate or lithium nickel cobalt aluminumate, or a combination of at least two thereof.

[0091] Preferably, the positive electrode active material is selected from lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP) and one of ternary materials represented by lithium nickel cobalt manganese oxide (NCM) and lithium nickel cobalt aluminum oxide (NCA).

[0092] However, the present application is not limited to these lithium-based positive electrode active materials, and other traditional materials that can be used as lithium battery positive electrode active materials can also be used in the present application. These lithium-based positive electrode active materials can be used alone or in combination of two or more.

[0093] In some embodiments, the negative electrode active material includes, but is not limited to, at least one of graphite, soft carbon, hard carbon, lithium titanate, or silicon-based materials.

[0094] The above-mentioned graphite includes artificial graphite and natural graphite; both hard carbon and soft carbon are disordered carbon materials; silicon-based materials mainly include at least one of carbon-coated silicon oxide composite materials and nano-silicon-carbon composite materials.

[0095] However, the present application is not limited to these negative electrode active materials, and other traditional materials that can be used as negative electrode active materials for lithium batteries can also be used in the present application. These negative electrode active materials can be used alone or in combination of two or more.

[0096] In the present application, the content of active materials and composite solid electrolytes in the intermediate transition layer 30 is different from the content of active materials and composite solid electrolytes in the electrode material layer 20, and the content of composite solid electrolytes in the electrode material layer 20 is less than the content of composite solid electrolytes in the intermediate transition layer 30.

[0097] Specifically, in some embodiments, in the electrode material layer 20, the mass fraction of the composite solid electrolyte is 0.1% to 5%, and the mass fraction of the active material is 95% to 99.9%. As an example, the mass fraction of the composite solid electrolyte in the electrode material layer 20 can be any point value of 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, or any range value between two of them; the mass fraction of the active material in the electrode material layer 20 can be any point value of 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 99%, 99.5%, 99.9%, or any range value between two of them.

[0098] In some embodiments, in the intermediate transition layer 30, the mass fraction of the composite solid electrolyte is 20% to 80%, and the mass fraction of the active material is 20% to 80%. As an example, the mass fraction of the composite solid electrolyte in the intermediate transition layer 30 can be any point value of 20%, 30%, 40%, 50%, 60%, 70%, 80%, or a range value between any two; the mass fraction of the active material in the intermediate transition layer 30 can be any point value of 20%, 30%, 40%, 50%, 60%, 70%, 80%, or a range value between any two.

[0099] In the present application, in the electrode material layer 20, the composite solid electrolyte can play a certain conductive and adhesive role. Therefore, the organic solid electrolyte with lithium conductivity and electrical conductivity in the composite solid electrolyte can be used as a conductive agent and a binder at the same time, and there is no need to add additional conductive agents and binders in the electrode material layer 20. The electrode material layer 20 can only include active materials and composite solid electrolytes, which simplifies the composition, reduces costs, optimizes the electrochemical properties of the electrode, and can also ensure conductivity and adhesion.

[0100] Similarly, the intermediate transition layer 30 may also only include active materials and composite solid electrolytes, and no additional conductive agent and binder need to be added to the intermediate transition layer 30. The solid electrolyte layer 40 may only include composite solid electrolytes.

[0101] In some embodiments, the thickness of the electrode material layer 20 is 30 μm to 150 μm. As an example, the thickness of the electrode material layer 20 can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, or a range consisting of any two of the above values.

[0102] By controlling the thickness of the electrode material layer 20 within the above range, the capacity of the battery can be guaranteed, and the lithium ion transmission rate can be improved, thereby avoiding the problem that the electrode material layer 20 is too thin or too thick and cannot take into account both the battery capacity and the charging rate.

[0103] In some embodiments, the thickness of the intermediate transition layer 30 is 0.1 μm to 5 μm. As an example, the thickness of the intermediate transition layer 30 can be 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or a range consisting of any two of the above values.

[0104] By making the thickness of the intermediate transition layer 30 within the above range, it can effectively play the role of intermediate transition, reduce the interface impedance, and improve the interface compatibility between the layers; avoid the intermediate transition layer 30 being too thin, which will weaken the effect of improving the interface compatibility, or avoid the intermediate transition layer 30 being too thick, which will increase the impedance.

[0105] In some embodiments, the thickness of the solid electrolyte layer 40 is 0.5 μm to 5 μm. As an example, the thickness of the solid electrolyte layer 40 can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 4 μm, 5 μm, or a range consisting of any two of the above values.

[0106] By making the thickness of the solid electrolyte layer 40 within the above range, the conductivity of the electrolyte system is optimized and the rate performance of the battery is improved.

[0107] In addition, in the present application, the specific type of the current collector 10 is not limited, and the current collector 10 can be selected from conventional types in the art. As an example, the current collector 10 can be stainless steel, aluminum, copper, nickel, titanium, fired carbon, or aluminum or stainless steel or copper surface-treated with one of carbon, nickel, titanium, silver, etc. In addition, the thickness of the current collector 10 can generally be 3 μm to 500 μm, and microscopic irregularities can be formed on the surface of the current collector 10 to enhance the adhesion of the active material. For example, the current collector 10 can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0108] Accordingly, in some embodiments, a method for preparing an electrode sheet is provided, the method comprising the following steps:

[0109] Providing electrode material layer 20 slurry and solid electrolyte layer 40 slurry respectively;

[0110] The electrode material layer 20 slurry and the solid electrolyte layer 40 slurry are sequentially coated on the current collector 10 to obtain an initial electrode sheet;

[0111] The initial electrode sheet is dried and hot rolled, and an electrode material layer 20, an intermediate transition layer 30 and a solid electrolyte layer 40 are sequentially formed on the current collector 10 to obtain an electrode electrode sheet, wherein the intermediate transition layer 30 is formed by the solid electrolyte layer 40 slurry coated on the electrode material layer 20 penetrating into the electrode material layer 20.

[0112] It should be understood that the “method for preparing the electrode plate” and the aforementioned “electrode plate” are based on the same inventive concept, and all the features and advantages described above for the “electrode plate” are also applicable to the “method for preparing the electrode plate” and will not be elaborated here one by one.

[0113] In the present application, in the process of preparing the electrode sheet, the slurry of the electrode material layer 20 and the slurry of the solid electrolyte layer 40 can be prepared separately first, and then the slurry of the electrode material layer 20 and the slurry of the solid electrolyte layer 40 are transported to the coating system for double-layer coating to form an initial electrode sheet with the lower layer being the electrode material layer 20, the middle layer being the intermediate transition layer 30, and the upper layer being the solid electrolyte layer 40; the initial electrode sheet is then dried and hot rolled to form a high-density, high-compacted flexible electrode sheet.

[0114] Among them, when preparing the slurry, only the slurry of the electrode material layer 20 and the slurry of the solid electrolyte layer 40 can be prepared, and the solid content and viscosity of the slurry of the electrode material layer 20 and the slurry of the solid electrolyte layer 40 are different; the intermediate transition layer 30 is formed by the slurry of the solid electrolyte layer 40 flowing downward due to the different solid content and viscosity of the slurry of the electrode material layer 20 and the slurry of the solid electrolyte layer 40, that is, the slurry of the solid electrolyte layer 40 can penetrate downward between coating and drying, thereby forming the intermediate transition layer 30. In this way, the operation is simple, the preparation is convenient, the process is simplified, the manufacturability is improved, and the preparation of the electrode material layer 20, the intermediate transition layer 30 and the solid electrolyte layer 40 can be realized without complex operations such as transfer and compounding; the obtained electrode sheet has the characteristics of high compaction density and good cycle performance.

[0115] Exemplarily, the preparation of the electrode sheet comprises the following steps:

[0116] S10, preparing a slurry for an electrode material layer.

[0117] Optionally, in step S10, a composite solid electrolyte having a certain ratio of active material, inorganic solid electrolyte and organic solid electrolyte with lithium conductivity and electrical conductivity is added to a solvent in a certain ratio, mixed and stirred to obtain a slurry of the electrode material layer.

[0118] In step S10 , the solvent includes, but is not limited to, at least one of N,N-dimethylacetamide (DMA), N-methylpyrrolidone (NMP), ethanol, acetone or water (such as deionized water).

[0119] In step S10, the solid content of the electrode material layer slurry is 50% to 85%, and the viscosity is 1500 to 8000 mPa·S; as an example, the solid content of the electrode material layer slurry can be 50%, 60%, 70%, 80%, 85% or a range consisting of any two of the above values; the viscosity of the electrode material layer slurry is 1500 mPa·S, 2000 mPa·S, 2500 mPa·S, 3000 mPa·S, 4000 mPa·S, 5000 mPa·S, 6000 mPa·S, 7000 mPa·S, 8000 mPa·S or a range consisting of any two of the above values.

[0120] By making the solid content and viscosity of the slurry of the electrode material layer within the above ranges, the uniformity of the slurry can be improved, and the coating surface density and coating quality can be ensured.

[0121] S20, preparing a slurry for a solid electrolyte layer.

[0122] Optionally, in step S20, an inorganic solid electrolyte and an organic solid electrolyte having lithium conductivity and electrical conductivity are added to a solvent in a certain proportion, mixed and stirred to prepare a slurry, so as to obtain a slurry of a solid electrolyte layer.

[0123] In step S20 , the solvent includes, but is not limited to, at least one of N,N-dimethylacetamide (DMA), N-methylpyrrolidone (NMP), ethanol or acetone.

[0124] In step S20, the solid content of the solid electrolyte layer slurry is 25% to 45%, and the viscosity is 100 to 2000 mPa·S; as an example, the solid content of the solid electrolyte layer slurry can be 25%, 30%, 35%, 40%, 45% or a range consisting of any two of the above values; the viscosity of the solid electrolyte layer slurry is 100 mPa·S, 200 mPa·S, 500 mPa·S, 800 mPa·S, 1000 mPa·S, 1500 mPa·S, 2000 mPa·S or a range consisting of any two of the above values.

[0125] By making the solid content and viscosity of the slurry of the solid electrolyte layer within the above range, the uniformity of the slurry can be improved, the coating surface density and coating quality can be guaranteed, and the slurry of the solid electrolyte layer can be easily penetrated downward to form the intermediate transition layer 30.

[0126] In step S20, the ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity in the composite solid electrolyte is consistent with the ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity in the composite solid electrolyte mixed in step S10.

[0127] S30, preparing an initial electrode.

[0128] Optionally, in step S30, the slurry of the electrode material layer and the slurry of the solid electrolyte layer obtained in the above steps S10 and S20 are transported to a coating system for double-layer coating to form an initial electrode sheet with the lower layer being the electrode material layer 20, the middle layer being the intermediate transition layer 30, and the upper layer being the solid electrolyte layer 40.

[0129] Optionally, in the initial electrode sheet obtained in step S30, the thickness of the electrode material layer 20 is 50 μm to 200 μm, for example, 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, etc.

[0130] Optionally, in the initial pole piece obtained in step S30, the thickness of the intermediate transition layer 30 is 0.1 μm to 10 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, etc.

[0131] Optionally, in the initial electrode obtained in step S30, the thickness of the solid electrolyte layer 40 is 1 μm to 10 μm, for example, 1 μm, 2 μm, 4 μm, 5 μm, 8 μm, 10 μm, etc.

[0132] The content of the composite solid electrolyte in the intermediate transition layer 30 of the initial electrode obtained in the above step S30 is 20wt% to 80wt%, and the ratio of the inorganic solid electrolyte to the organic solid electrolyte with lithium conductivity and electrical conductivity is consistent with that in the electrode material layer 20 and the solid electrolyte layer 40.

[0133] S40, preparing electrode plates.

[0134] Optionally, in step S40, the initial electrode sheet obtained in step S30 is dried and hot rolled to form a high-density, high-compacted flexible electrode sheet.

[0135] Optionally, in step S40, the drying temperature is 50°C to 130°C; for example, it may be 50°C, 60°C, 80°C, 100°C, 110°C, 130°C, etc.

[0136] In the rolled electrode sheet obtained in step S40 , the thickness of the electrode material layer 20 is 30 μm to 150 μm.

[0137] In the rolled electrode sheet obtained in step S40 , the thickness of the intermediate transition layer 30 is 0.1 μm to 5 μm.

[0138] In the rolled electrode sheet obtained in step S40 , the thickness of the solid electrolyte layer 40 is 0.5 μm to 5 μm.

[0139] In the present application, the preparation of the organic solid electrolyte having lithium conductivity and electrical conductivity can be prepared by a method known in the art. As an example, the organic solid electrolyte having lithium conductivity and electrical conductivity is a copolymer, such as a block copolymer having an AB structure, and the preparation of the copolymer includes:

[0140] bringing the lithium-conducting polymer, the solvent and the isocyanate monomer into first contact to obtain a viscous solution;

[0141] The viscous solution, the conductive polymer monomer, the initiator and the solvent are brought into second contact to generate a polymerization reaction to obtain a first material;

[0142] Post-processing the first material to obtain a block copolymer having an AB structure;

[0143] Among them, A is a conductive unit, B is a lithium conductive unit, the conductive unit includes a conductive polymer monomer, and the lithium conductive unit includes a lithium conductive polymer.

[0144] The block copolymer with AB structure can be prepared by chemical oxidative polymerization, and has the characteristics of simple operation, easy regulation, and easy industrial application.

[0145] Optionally, the isocyanate monomer may be selected from toluene diisocyanate (TDI), or may be selected from other isocyanate monomers, which is not limited.

[0146] Optionally, the conditions for the first contact include: magnetic stirring at 60°C to 80°C (such as 60°C, 70°C, 80°C, etc.) for 2h to 6h (such as 2h, 3h, 4h, 6h, etc.).

[0147] Optionally, the above post-processing may include filtering, cleaning and other operations.

[0148] The following mainly takes the conductive polymer monomer selected from ANI and the lithium-conducting polymer selected from PEG as an example to explain in detail the preparation process of the copolymer. It should be understood that the same or similar principles apply when selecting other conductive polymer monomers and lithium-conducting polymers, which are not listed one by one here.

[0149] Exemplarily, the preparation of a block copolymer having an AB structure comprises the following steps:

[0150] (1) At room temperature and under an inert atmosphere (such as argon), dissolve 1.0 g of PEG (polyethylene glycol) in 10 mL of DMF solution to obtain a solution.

[0151] (2) The solution obtained in step (1) was added dropwise to 0.21 g TD (toluene diisocyanate) (1.2 mmol), and the mixture was stirred magnetically at 70 °C for 4 h to obtain a viscous solution.

[0152] (3) The viscous solution obtained in step (2) was cooled to room temperature and then added dropwise to a 5 mL DMF solution containing PPD (biphenyl-4-carboxylic acid) (1 mmol), and stirred at 70° C. for 4 h to obtain a mixture solution.

[0153] (4) The mixture solution in step (3) is cooled to room temperature, and then repeatedly precipitated with diethyl ether to obtain an ANI (aniline) functionalized PEG colloidal substance.

[0154] (5) Dissolving the ANI-functionalized PEG colloidal substance prepared in step (4) in acetone to obtain a suspension.

[0155] (6) Add ANI to HCl solution (0.1 M) and stir magnetically in an ice bath.

[0156] (7) Precooled APS (ammonium persulfate) (the molar ratio of APS to ANI added in step (6) is 1:1.2) and 0.1 M HCl solution are added dropwise to the suspension in step (5) and stirred at 5°C for 4 h. The PEG-PANI copolymer is obtained by filtration and washing, that is, a block copolymer having an AB structure is obtained. The molecular structure diagram of the formed block copolymer (PEG-PANI) is shown in FIG. Figure 2 shown.

[0157] In some embodiments, a battery is provided, the battery comprising a positive electrode sheet, a negative electrode sheet and a separator;

[0158] Wherein, the positive electrode sheet and / or the negative electrode sheet comprises the aforementioned electrode sheet or the electrode sheet prepared according to the aforementioned method.

[0159] In the present application, the battery may be a solid-state battery, for example, the battery may be a lithium-ion battery, and further, the battery may be a lithium-ion semi-solid-state battery.

[0160] In the above battery, the positive electrode sheet may be the electrode sheet provided in any of the aforementioned embodiments, or the negative electrode sheet may be the electrode sheet provided in any of the aforementioned embodiments, or both the positive electrode sheet and the negative electrode sheet may be the electrode sheet provided in any of the aforementioned embodiments.

[0161] The present application has no particular limitation on the isolation membrane, as long as the purpose of the present application can be achieved.

[0162] Optionally, the battery may further include an electrolyte, which may be an electrolyte solution, which includes a lithium salt and an organic solvent. The present application has no particular restrictions on the lithium salt and the organic solvent, as long as the purpose of the present application can be achieved.

[0163] The present application can reduce the use of liquid electrolyte by mixing a composite solid electrolyte into the electrode plate, thereby greatly enhancing the safety performance of the battery.

[0164] Optionally, the above-mentioned battery, such as a lithium-ion semi-solid battery, can be prepared by the following preparation method:

[0165] The electrode sheets, such as the flexible composite positive electrode sheets, the separator, and the electrode sheets, such as the flexible composite negative electrode sheets, are stacked / winded to obtain bare cells, the positive and negative electrode tabs are welded, the bare cells are packed with aluminum-plastic film battery cases (or aluminum battery cases / steel battery cases / nickel-plated battery cases), liquid is injected, packaged, allowed to stand, formed, and capacity divided to obtain lithium-ion semi-solid-state batteries.

[0166] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0167] In summary, the electrode plate, the preparation method of the electrode plate and the battery provided by the present invention, through the coordinated arrangement of the above-mentioned electrode material layer 20, the intermediate transition layer 30 and the solid electrolyte layer 40, strengthen the extremely strong interface compatibility and adhesion between the flexible positive and negative electrode plates, and can effectively cope with the volume, internal stress and electrode structure changes caused by the charge and discharge cycle of the lithium-ion solid-state battery; thereby improving the coulomb efficiency and cycle life of the lithium-ion solid-state battery. Performance. By regulating the resistance and surface charge transfer resistance of electrons and ions along the path from the deposition point to the current collector, the transfer and deposition of lithium ions in the plate are promoted. In addition, the flexible composite electrode plate with high ionic conductivity and electronic conductivity provided by the present invention has a simple preparation process, low cost, is suitable for scaled-up production, and has strong adaptability and universality. The electrode plate can realize a high-energy-density lithium-ion solid-state battery with high nickel ternary as the positive electrode and silicon carbon / silicon oxygen as the negative electrode at a high rate for a long-term stable cycle.

[0168] The test shows that the lithium-ion solid-state battery cycle performance of the electrode sheet (flexible composite high-nickel positive electrode sheet) and silicon-carbon negative electrode prepared by the present invention is that the battery capacity retention rate SOH is about 88% after 2400 cycles, that is, 2400 cycles @ 88% SOH, and it is expected to reach 3600 cycles @ 80% SOH. In addition, the lithium-ion solid-state battery of the electrode sheet (flexible composite high-nickel positive electrode sheet) and silicon-carbon negative electrode prepared by the present invention can pass the 150°C hot box test.

[0169] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.

[0170] Example 1

[0171] 1. Preparation of electrode sheet (positive electrode sheet)

[0172] S10. Prepare slurry for electrode material layer: place ternary positive electrode material NCM and composite solid electrolyte (mass proportion of composite solid electrolyte is 2%) in a high-speed blender, wherein the composite solid electrolyte comprises 50% by mass of inorganic solid electrolyte LATP and 50% by mass of organic solid electrolyte PEG-PANI copolymer (conductive polymer monomer is ANI, lithium conductive polymer is PEG) with lithium conductivity and electrical conductivity, then add NMP into the high-speed blender, stir and mix, and obtain slurry for electrode material layer with solid content of 70% and viscosity of 4500 mPa·S.

[0173] S20. Prepare a slurry for a solid electrolyte layer: place 50% by weight of an inorganic solid electrolyte LATP and 50% by weight of an organic solid electrolyte PEG-PANI copolymer (the conductive polymer monomer is ANI and the lithium conductive polymer is PEG) having lithium conductivity and electrical conductivity in a high-speed blender, then add the NMP solution into the high-speed blender, stir and mix, and obtain a slurry for a solid electrolyte layer having a solid content of 35% and a viscosity of 1500 mPa·S.

[0174] S30, conveying the slurry of the electrode material layer and the slurry of the solid electrolyte layer obtained in step S10 and step S20 to the coating system for double-layer coating, to form an initial electrode sheet with a lower layer of 120 μm thick electrode material layer, a middle layer of 5 μm thick intermediate transition layer, and an upper layer of 5 μm thick solid electrolyte layer; wherein the intermediate transition layer is formed by the solid electrolyte layer slurry coated on the electrode material layer penetrating downward, and the mass content of the composite solid electrolyte in the intermediate transition layer is 45%.

[0175] S40, drying and hot rolling the initial electrode sheet obtained in step S30 to form a high-density, high-compacted flexible electrode sheet; in the electrode sheet after rolling, the thickness of the electrode material layer is 85 μm, the thickness of the intermediate transition layer is 3.5 μm, and the thickness of the solid electrolyte layer is 3.5 μm.

[0176] 2. Preparation of batteries, including:

[0177] Use a cutting machine to cut the positive electrode sheet into 12 mm round positive electrode sheets;

[0178] A negative electrode sheet is formed by using a negative electrode active material layer including graphite, a negative electrode active material, and a negative electrode current collector;

[0179] Ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent at a ratio of 1.5 mol / L to prepare an electrolyte;

[0180] Polyethylene (PE) with a thickness of 7 μm is used as the diaphragm;

[0181] The positive electrode sheet, separator and negative electrode sheet are wound to obtain a bare cell, the positive and negative electrode tabs are welded, the bare cell is packed in an aluminum-plastic film battery shell, and then the lithium-ion solid-state battery is obtained through processes such as liquid injection, packaging, standing, formation and capacity division.

[0182] Example 2

[0183] 1. Preparation of electrode sheet (positive electrode sheet)

[0184] S10. Prepare slurry for electrode material layer: place ternary positive electrode material NCM and composite solid electrolyte (the mass proportion of composite solid electrolyte is 2%) in a high-speed blender, wherein the composite solid electrolyte comprises 80% by mass of inorganic solid electrolyte LATP and 20% by mass of organic solid electrolyte PEG-PANI copolymer with lithium conductivity and electrical conductivity, then add NMP into the high-speed blender, stir and mix, and obtain slurry for electrode material layer with solid content of 70% and viscosity of 4000 mPa·S.

[0185] S20. Prepare a slurry for a solid electrolyte layer: place 80% by weight of an inorganic solid electrolyte LATP and 20% by weight of an organic solid electrolyte PEG-PANI copolymer having lithium conductivity and electrical conductivity in a high-speed blender, then add an NMP solution into the high-speed blender, stir and mix, and obtain a slurry for a solid electrolyte layer having a solid content of 35% and a viscosity of 1100 mPa·S.

[0186] S30, conveying the slurry of the electrode material layer and the slurry of the solid electrolyte layer obtained in step S10 and step S20 to the coating system for double-layer coating, to form an initial electrode sheet with a lower layer of 120 μm thick electrode material layer, a middle layer of 6 μm thick intermediate transition layer, and an upper layer of 8 μm thick solid electrolyte layer; wherein the intermediate transition layer is formed by the downward penetration of the solid electrolyte layer slurry coated on the electrode material layer, and the mass content of the composite solid electrolyte in the intermediate transition layer is 65%.

[0187] S40, drying and hot rolling the initial electrode sheet obtained in step S30 to form a high-density, high-compacted flexible electrode sheet; in the electrode sheet after rolling, the thickness of the electrode material layer is 85 μm, the thickness of the intermediate transition layer is 4.25 μm, and the thickness of the solid electrolyte layer is 5.6 μm.

[0188] The rest are the same as in Example 1.

[0189] Example 3

[0190] The main differences between Example 3 and Example 1 are:

[0191] S30, respectively conveying the slurry of the electrode material layer and the slurry of the solid electrolyte layer obtained in step S10 and step S20 to the coating system for double-layer coating to form an initial electrode sheet with a lower layer of a 180 μm thick electrode material layer, a middle layer of a 7.5 μm thick intermediate transition layer, and an upper layer of a 7.5 μm thick solid electrolyte layer.

[0192] S40, drying and hot rolling the initial electrode sheet obtained in step S30 to form a high-density, high-compacted flexible electrode sheet; in the electrode sheet after rolling, the thickness of the electrode material layer is 126 μm, the thickness of the intermediate transition layer is 5.25 μm, and the thickness of the solid electrolyte layer is 5.25 μm.

[0193] The rest are the same as in Example 1.

[0194] Example 4

[0195] The main differences between Example 4 and Example 1 are:

[0196] In step S10, the composite solid electrolyte includes 30% by weight of an inorganic solid electrolyte LATP and 70% by weight of an organic solid electrolyte PEG-PANI copolymer having lithium conductivity and electrical conductivity; the slurry of the electrode material layer has a solid content of 65% and a viscosity of 5000 mPa·S.

[0197] In step S20, the composite solid electrolyte includes 30% by weight of an inorganic solid electrolyte LATP and 70% by weight of an organic solid electrolyte PEG-PANI copolymer having lithium conductivity and electrical conductivity; the slurry solid content of the solid electrolyte layer is 38% and the viscosity is 1800 mPa·S.

[0198] The rest are the same as in Example 1.

[0199] Example 5

[0200] The main differences between Example 5 and Example 1 are:

[0201] In step S10, the composite solid electrolyte includes 90% by weight of an inorganic solid electrolyte LATP and 10% by weight of an organic solid electrolyte PEG-PANI copolymer having lithium conductivity and electrical conductivity; the slurry of the electrode material layer has a solid content of 75% and a viscosity of 4000 mPa·S.

[0202] In step S20, the composite solid electrolyte includes 90% by weight of an inorganic solid electrolyte LATP and 10% by weight of an organic solid electrolyte PEG-PANI copolymer having lithium conductivity and electrical conductivity; the slurry solid content of the solid electrolyte layer is 42% and the viscosity is 1000 mPa·S.

[0203] The rest are the same as in Example 1.

[0204] Example 6

[0205] The main differences between Example 6 and Example 1 are:

[0206] In step S10, the mass proportion of the composite solid electrolyte in the electrode material layer is 1%;

[0207] In step S30, the mass proportion of the composite solid electrolyte in the intermediate transition layer is 20%.

[0208] The rest are the same as in Example 1.

[0209] Example 7

[0210] The difference between Example 7 and Example 1 is mainly that:

[0211] In step S10, the mass proportion of the composite solid electrolyte in the electrode material layer is 5%;

[0212] In step S30, the mass proportion of the composite solid electrolyte in the intermediate transition layer is 75%.

[0213] The rest are the same as in Example 1.

[0214] Example 8

[0215] The difference between Example 8 and Example 1 is mainly that:

[0216] In steps S10 and S20, the inorganic solid electrolyte uses LLZO.

[0217] The rest are the same as in Example 1.

[0218] Example 9

[0219] The main differences between Example 9 and Example 1 are:

[0220] In steps S10 and S20, the organic solid electrolyte having lithium and electrical conductivity is a PEO-PPTA copolymer (the conductive polymer monomer is PTA and the lithium conductive polymer is PEO).

[0221] The rest are the same as in Example 1.

[0222] Example 10

[0223] The main differences between Example 10 and Example 1 are:

[0224] In steps S10 and S20, the organic solid electrolyte having lithium-conducting and electrical-conducting capabilities adopts a PPO-PANI copolymer (the conductive polymer monomer is ANI and the lithium-conducting polymer is PPO).

[0225] The rest are the same as in Example 1.

[0226] Comparative Example 1

[0227] The difference between Comparative Example 1 and Example 1 is mainly that:

[0228] Step S20 is omitted, and step S30 is a single-layer coating.

[0229] That is, the positive electrode sheet obtained in Comparative Example 1 does not have an intermediate transition layer and a solid electrolyte layer, and the positive electrode sheet only includes a current collector and an electrode material layer disposed on the current collector.

[0230] The rest are the same as in Example 1.

[0231] Comparative Example 2

[0232] The difference between Comparative Example 2 and Example 1 is mainly that:

[0233] The composite solid electrolyte in step S10 is omitted.

[0234] That is, the electrode material layer in the electrode plate obtained in Comparative Example 2 only contains active materials, and the intermediate transition layer only contains active materials.

[0235] The rest are the same as in Example 1.

[0236] Comparative Example 3

[0237] The difference between Comparative Example 3 and Example 1 is mainly that:

[0238] The organic solid electrolyte having lithium and electrical conductivity in step S10 and step S20 is omitted.

[0239] That is, in the electrode plate obtained in Comparative Example 3, the solid electrolyte in the electrode material layer, the intermediate transition layer and the solid electrolyte layer is only an inorganic solid electrolyte.

[0240] The rest are the same as in Example 1.

[0241] Comparative Example 4

[0242] The difference between Comparative Example 4 and Example 1 is mainly that:

[0243] The intermediate transition layer is omitted.

[0244] That is, the electrode plate obtained in Comparative Example 4 only includes a current collector and an electrode material layer and a solid electrolyte layer disposed on the current collector.

[0245] The rest are the same as in Example 1.

[0246] Performance Testing

[0247] 1. Test of electrode plates

[0248] The electrode plates (positive electrode plates) obtained in the above-mentioned embodiments and comparative examples were subjected to a plate flexibility performance test.

[0249] Pole piece flexibility (bending times) test: The positive pole pieces of each embodiment and comparative example were cut into 20×150 mm long strips. Under normal temperature, each positive pole piece was folded in half until foil leakage and light leakage occurred on the pole piece, and the bending times of the positive pole piece were recorded.

[0250] The test results are shown in Table 1 below.

[0251] Table 1 Performance test results of the positive electrode sheets of various embodiments and comparative examples

[0252]

[0253] It can be seen from the data in Table 1 that, in general, the positive electrode sheets prepared in Examples 1-10 of the present invention have enhanced flexibility compared to the positive electrode sheets of Comparative Examples 1-4. In particular, the intermediate transition layer and the solid electrolyte layer are omitted in the positive electrode sheet of Comparative Example 1, which greatly reduces the flexibility of the sheet, has poor interface compatibility, and increases interface impedance. Comparative Example 3 omits the organic solid electrolyte with lithium and electrical conductivity, which also reduces the flexibility of the sheet, has poor interface compatibility, and increases interface impedance.

[0254] 2. Testing of Lithium-ion Solid-state Batteries

[0255] The lithium-ion batteries obtained in the above-mentioned embodiments and comparative examples were subjected to cycle capacity retention rate test and hot box test.

[0256] (1) Cycle capacity retention rate test: The batteries of the embodiments and comparative examples were charged at 1C constant current to 4.25V at room temperature, then charged at 4.25V constant voltage until the current reached 0.05C cut-off, left to stand, and then discharged at 0.33C constant current to 2.8V. The discharge capacity at the first cycle was recorded as the initial capacity, and the capacity retention rates at 500, 1000, and 2400 cycles were recorded respectively. The capacity retention rate at the nth cycle = discharge capacity at the nth cycle / discharge capacity at the first cycle * 100%, where n is 500, 1000, or 2400.

[0257] (2) Hot box test: Starting from 100% SOC of the battery, the temperature box is heated to (130±2)℃ at a heating rate of 5℃ / min and maintained at this temperature for 30 minutes. The temperature box is heated to (140±2)℃ at a heating rate of 5℃ / min and maintained at this temperature for 30 minutes. The temperature box is heated to (150±2)℃ at a heating rate of 5℃ / min and maintained at this temperature for 30 minutes. If the battery does not catch fire or explode within 30 minutes of constant temperature, it means that it has passed the hot box test at this temperature.

[0258] The test results are shown in Table 2 below.

[0259] Table 2 Battery performance test results of various embodiments and comparative examples

[0260] It can be seen from the data in Table 2 that the lithium-ion solid-state battery using the positive electrode plates provided in Examples 1-10 of the present invention plays a positive role in improving the cycle performance and safety performance (characterized by hot box testing) of the battery.

[0261] At the same time, it can be seen from the data in the above table that Example 1 omits the intermediate transition layer and the solid electrolyte layer, which reduces the flexibility of the pole piece, poor interface compatibility, increased interface impedance, and also reduces the cycle performance of the battery. Example 2 omits the composite solid electrolyte in the electrode material layer and the intermediate transition layer, resulting in a lithium ion migration channel without a solid electrolyte in the electrode material layer and the intermediate transition layer, and the lithium ion kinetic performance is low, which reduces the cycle performance of the battery. Examples 3 and 4 also reduce the cycle performance to a certain extent, indicating that their interface impedance is large, which reduces the ion conduction and electronic conduction capabilities of lithium ions at the interface between the positive and negative electrodes. In addition, Examples 1 to 4 all failed the 130°C hot box test, which reduced safety, indicating that the embodiments of the present invention can greatly improve the safety of lithium-ion solid-state batteries.

[0262] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0263] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0264] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0265] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0266] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrode plate, characterized in that: The electrode plate comprises: current collector; An electrode material layer, disposed on at least one side surface of the current collector along the thickness direction, the electrode material layer comprising an active material and a composite solid electrolyte; An intermediate transition layer, disposed on a surface of the electrode material layer away from the current collector, the intermediate transition layer comprising an active material and a composite solid electrolyte; and A solid electrolyte layer is arranged on a surface of the intermediate transition layer away from the electrode material layer, and the solid electrolyte layer includes a composite solid electrolyte; The composite solid electrolyte comprises an inorganic solid electrolyte and an organic solid electrolyte having lithium conductivity and electrical conductivity; the organic solid electrolyte having lithium conductivity and electrical conductivity comprises a copolymer, and the copolymer is a block copolymer having an AB structure, wherein A is a conductive unit and B is a lithium conductive unit; The content of the composite solid electrolyte in the intermediate transition layer is greater than the content of the composite solid electrolyte in the electrode material layer; The active material in the electrode material layer and the active material in the intermediate transition layer are of the same type; the inorganic solid electrolyte and the organic solid electrolyte having lithium conductivity and electrical conductivity in the electrode material layer, the intermediate transition layer and the solid electrolyte layer are in the same mass ratio; The intermediate transition layer is formed by the solid electrolyte layer slurry coated on the electrode material layer penetrating into the electrode material layer.

2. The electrode plate according to claim 1, characterized in that: The conductive unit includes a conductive polymer monomer, and the lithium conductive unit includes a lithium conductive polymer; The conductive polymer monomer includes at least one of pyrrole, aniline, thiophene, acetylene, p-phenylene terephthalamide or 3,4-ethylenedioxythiophene; and / or, The lithium-conducting polymer includes at least one of polyethylene oxide, polyethylene glycol, polypropylene oxide, poly(ethylene glycol) acrylate or poly(ethylene glycol) methacrylate.

3. The electrode plate according to claim 1, characterized in that: In the electrode material layer, the mass proportion of the composite solid electrolyte is 0.1% to 5%, and the mass proportion of the active material is 95% to 99.9%; and / or, In the intermediate transition layer, the mass proportion of the composite solid electrolyte is 20% to 80%, and the mass proportion of the active material is 20% to 80%.

4. The electrode plate according to claim 1, characterized in that: The inorganic solid electrolyte comprises an oxide solid electrolyte, wherein the oxide solid electrolyte comprises at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide or lithium lanthanum titanate; and / or, The active material is a positive electrode active material or a negative electrode active material; The positive electrode active material comprises at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium cobalt manganese oxide, lithium cobalt nickel oxide, lithium nickel manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide; and / or, The negative electrode active material includes at least one of graphite, soft carbon, hard carbon, lithium titanate or silicon-based materials.

5. The electrode plate according to claim 1, characterized in that: In the composite solid electrolyte in the electrode material layer, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is x, and x is (5-95): (95-5); and / or, In the composite solid electrolyte in the intermediate transition layer, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is y, and y is (5-95): (95-5); and / or, In the composite solid electrolyte in the solid electrolyte layer, the mass ratio of the inorganic solid electrolyte to the organic solid electrolyte having lithium conductivity and electrical conductivity is z, and z is (5-95): (95-5); Wherein, the x, y and z are the same.

6. The electrode plate according to any one of claims 1 to 5, characterized in that: The thickness of the electrode material layer is 30 μm to 150 μm; and / or, The thickness of the intermediate transition layer is 0.1 μm to 5 μm; and / or, The thickness of the solid electrolyte layer is 0.5 μm to 5 μm.

7. The method for preparing an electrode sheet according to any one of claims 1 to 6, characterized in that: The following steps are involved: Providing electrode material layer slurry and solid electrolyte layer slurry respectively; sequentially coating the electrode material layer slurry and the solid electrolyte layer slurry on the current collector to obtain an initial electrode sheet; The initial electrode sheet is dried and hot rolled, and an electrode material layer, an intermediate transition layer and a solid electrolyte layer are sequentially formed on the current collector to obtain an electrode electrode sheet, wherein the intermediate transition layer is formed by the solid electrolyte layer slurry coated on the electrode material layer penetrating into the electrode material layer.

8. The method for preparing an electrode sheet according to claim 7, characterized in that: The preparation method satisfies at least one of the following characteristics (1) to (8): (1) The solvent in the electrode material layer slurry includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, acetone or water; (2) The solvent in the solid electrolyte layer slurry includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, ethanol or acetone; (3) The solid content of the electrode material layer slurry is 50% to 85%, and the viscosity is 1500 to 8000 mPa·S; (4) The solid content of the solid electrolyte layer slurry is 25% to 45%, and the viscosity is 100 to 2000 mPa·S; (5) The drying temperature is 50°C to 130°C; (6) In the initial electrode sheet, the thickness of the electrode material layer is 50 μm to 200 μm; And / or, in the electrode plate, the thickness of the electrode material layer is 30 μm to 150 μm; (7) In the initial pole piece, the thickness of the intermediate transition layer is 0.1 μm to 10 μm; and / or, in the electrode pole piece, the thickness of the intermediate transition layer is 0.1 μm to 5 μm; (8) In the initial electrode sheet, the thickness of the solid electrolyte layer is 1 μm to 10 μm; and / or, in the electrode electrode sheet, the thickness of the solid electrolyte layer is 0.5 μm to 5 μm.

9. The method for preparing an electrode sheet according to claim 7 or 8, characterized in that: The electrode material layer slurry and the solid electrolyte layer slurry both contain an organic solid electrolyte having lithium conductivity and electrical conductivity, and the organic solid electrolyte having lithium conductivity and electrical conductivity includes a copolymer, and the preparation of the copolymer includes: bringing the lithium-conducting polymer, the solvent and the isocyanate monomer into first contact to obtain a viscous solution; The viscous solution, the conductive polymer monomer, the initiator and the solvent are brought into second contact to generate a polymerization reaction to obtain a first material; Post-processing the first material to obtain a block copolymer having an AB structure; Among them, A is a conductive unit, B is a lithium conductive unit, the conductive unit includes a conductive polymer monomer, and the lithium conductive unit includes a lithium conductive polymer.

10. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and a separator; Wherein, the positive electrode sheet and / or the negative electrode sheet comprises the electrode sheet according to any one of claims 1 to 6 or the electrode sheet prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Composite polymer and preparation method and application thereof

    CN111423577A

  • Positive electrode and electrochemical device comprising same

    CN113782708A